(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Room attendants are responsible for maintaining rooms tidy and friendly. However, overwork can lead to stress, exhaustion, body aches, and sickness. This can have an adverse effect on employee performance, making it harder to accomplish goals. The purpose of this study is to determine the factors affecting working performance among room attendants at SOGO Novaliches Quezon City in terms of company culture, employee engagement, job satisfaction, and training and development. The result of this study reveals that among room attendants at sogo hotel experience, the factors affecting working performance are evaluated as “Affected” in terms of company culture, employee engagement, job satisfaction, and training and development; the problem encountered by the room attendant in terms of guest relation, diversity of guest, handling the guest request, communication skills, and supplies and materials are also affected the working performance of room attendant. The possible solution and strategy for a room attendant to cope with daily tasks to maintain good working performance in the housekeeping department and how the way the findings can be utilized in crafting a guide for factors affecting working performance among room attendants are also evaluated as “affected.” This will help to practice and improve the performance of room attendants to cope with the task. This study recommended that room attendant must improve their working performance and cope with the factors that affect performance, such as company culture, employee engagement, job satisfaction, and training and development. It is a must to encourage and promote the employee to have a good working performance.